Body mass index and quality of life in individuals with polycystic ovary syndrome: Dysmorphic concerns and eating disorders as mediators - Barberis, Nadia; Calaresi, Danilo; Cannavò, Marco; Verrastro, Valeria (Frontiers in Public Health, 2022)
Objective Weight issues, dysmorphic concerns and eating disorders are common among individuals with polycystic ovary syndrome (PCOS) and are linked to poor quality of life (QoL). The goal of the current study was to examine whether the association between body mass index (BMI) and QoL was mediated by dysmorphic concerns, examining also the relations with eating disorder symptomatology. Methods Questionnaires were administered to 435 individuals with PCOS aged between 18 and 40 years (M = 27.62; SD = 4.83) to measure dysmorphic concerns, eating disorder symptoms and QoL. Participants were also asked to report their height and weight to compute their BMI. Results Structural equation modeling was used to observe the relationship between the variables. The results revealed a direct relationship between QoL, BMI, dysmorphic concerns and eating disorder symptomatology. In addition, dysmorphic concerns were related to BMI and eating disorder symptomatology. Furthermore, the results showed the mediating role of dysmorphic concerns and eating disorder symptoms in the relationship between BMI and QoL. Conclusion The current results highlight the potential importance of harmful relationships with one's own body and food, explaining why weight issues may be linked to different levels of QoL in PCOS individuals. The implications of these findings are discussed.